Coming full circle: Past, present, and future research on ethnic‐racial socialization. (22nd December 2021) - Niwa, Erika Y.; Hughes, Diane L.; Ruck, Martin D.
Abstract: When this special issue was first proposed in 2019, we endeavored to push forward scholarship about the various ways in which individuals, interactions, and settings communicate messages to children and youth about ethnicity and race. In particular, we aimed to broaden the scope of our current understanding of ethnic‐racial socialization through the inclusion of theory and research that took a more expansive approach. We sought papers focused on multiple agents of socialization, including settings, that also (a) featured diverse ethnic‐racial groups and national contexts, (b) covered a wide swath of development, from early childhood through emerging adulthood, (c) employed varied methodological approaches, and (d) centered intersectional perspectives. As the world continues to change shape in the face of the ongoing Covid‐19 pandemic and broad‐based racial justice movements, this special issue feels ever more urgent and pressing. The articles presented in this special issue are diverse and expansive in their focus, approach, content, and findings. Yet, despite their breadth, they offer critical insight into three key questions facing the study of ethnic‐racial socialization: Where are we coming from? Where are we now? And where are we headed?